THE ANALYSIS OF THE SOCIO-POLITICAL FICTION NOVELS UNDER BINARY OPPOSITION (CASE STUDY OF INDONESIAN NOVEL ENTITLED "ORANG-ORANG PROYEK" BY AHMAD TOHARI) - Abdul Muqit (Informasi, 2019)
The socio-political fiction novel is generally realistic and gives an implicit picture of the social environment of a place. This type of reading is less popular because it is difficult to interpret and is also of less interest to readers than other literature. One of the works that can reflect this literary type is the novel entitled “Orang-Orang Proyek” by Ahmad Tohari, which represents the real condition of the Indonesian community under their politic and social circumstances. This paper tries to break down the literary work using the deconstructive-reading method to read a text with multi-interpretation understanding where the version contains many probabilities of meaning. This study will be able to provide insight into the correct reading method according to the purpose and type of literacy used in literary works.  Novel fiksi sosial-politik umumnya realistis dan memberikan gambaran implisit tentang lingkungan sosial suatu tempat. Jenis bacaan ini kurang populer karena sulit untuk ditafsirkan dan juga kurang menarik bagi pembaca daripada literatur lainnya. Salah satu karya yang dapat mencerminkan jenis sastra ini adalah novel berjudul “Orang-Orang Proyek” oleh Ahmad Tohari, yang mewakili kondisi nyata masyarakat Indonesia di bawah kondisi sosial dan politik mereka. Makalah ini mencoba untuk memecah karya sastra menggunakan metode membaca dekonstruktif untuk membaca teks dengan pemahaman multi-interpretasi di mana representasi mengandung banyak kemungkinan makna. Penelitian ini akan dapat memberikan wawasan tentang metode membaca yang benar sesuai dengan tujuan dan jenis literasi yang digunakan dalam karya sastra.